2011
DOI: 10.1653/024.094.0441
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Identification and Phylogeny ofBactroceraSpecies (Diptera: Tephritidae)

Abstract: BioOne Complete (complete.BioOne.org) is a full-text database of 200 subscribed and open-access titles in the biological, ecological, and environmental sciences published by nonprofit societies, associations, museums, institutions, and presses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(21 citation statements)
references
References 21 publications
0
21
0
Order By: Relevance
“…In our study, Ceratitis capitata was chosen as an outgroup because it belongs to the subfamily Dacinae, shown to be closely related to Bactrocera genus rather than Anastrepha spp. Previous research by Asokan et al (2011) also used C. capitata and A. ludens as outgroups to infer phylogenetic trees in Bactrocera spp.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study, Ceratitis capitata was chosen as an outgroup because it belongs to the subfamily Dacinae, shown to be closely related to Bactrocera genus rather than Anastrepha spp. Previous research by Asokan et al (2011) also used C. capitata and A. ludens as outgroups to infer phylogenetic trees in Bactrocera spp.…”
Section: Discussionmentioning
confidence: 99%
“…The infestation of Bactrocera species consequently reduces production yields and the quality of the crops (Chua et al 2010). Therefore, accurate identification of Bactrocera species is highly important for the successful management of targeted pest and quarantine initiatives (Asokan et al 2011;Liu et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The documented information indicates that very limited studies have been done to date on B. zonata population genetic structure and geographical variability based on partial mtCOI gene sequences, barring few studies that have focused on very vague aspects of genetic distance between populations of B. zonata with many other pairs of distinctly different Bactrocera species (Muraji and Nakahara, 2001;Nakahara and Muraji, 2008;Zhang et al, 2010;Asokan et al, 2011). A promising, but still preliminary study on RT-PCR of partial mtCOI gene sequence from B. zonata in Egypt by Abd-El-Samie and El Fiky (2011) established mitochondrial sequence data.…”
Section: Introductionmentioning
confidence: 99%
“…Han and Ro (2009) reconfirmed monophyly of subfamily Dacinae using 12s, 16s and COII gene fragments. Asokan et al (2011) and Yong et al (2015) revealed monophyly of Bactrocera using COI and 13 protein coding genes, respectively. Krosch et al (2012)…”
Section: Phylogenymentioning
confidence: 99%